Identification of Homologous Polyprenols from Thermophilic Bacteria - Gharwalová, Lucia; Palyzová, Andrea; Marešová, Helena; Kolouchová, Irena; Kyselová, Lucie; Řezanka, Tomáš (Microorganisms, 2021)
Sixteen strains of five genera of thermophilic bacteria, i.e., Alicyclobacillus, Brevibacillus, Geobacillus, Meiothermus, and Thermus, were cultivated at a temperature from 42 to 70 °C. Twelve strains were obtained from the Czech Collection of Microorganisms, while four were directly isolated and identified by 16S rRNA gene sequencing from the hot springs of the world-famous Carlsbad spa (Czech Republic). Polyprenol homologs from C40 to C65 as well as free undecaprenol (C55), undecaprenyl phosphate, and undecaprenyl diphosphate were identified by shotgun analysis and RP-HPLC/MS-ESI+ (reverse phase high-performance liquid chromatography-high-resolution positive electrospray ionization mass spectrometry). The limit of detection (50 pM) was determined for individual homologs and free polyprenols and their phosphates. Thus, it has been shown that at least some thermophilic bacteria produce not just the major C55 polyprenol as previously described, but a mixture of homologs.
Keywords: Geobacillus stearothermophilus; liquid chromatography-mass spectrometry; high resolution electrospray MS; thermophilic bacteria; polyprenols